(untitled) (Jurnal Common, 2024)
A real-life case at a well-known media company, Fox News in 2016, which was later made into a movie titled "Bombshell." This incident sparked the researcher’s interest in exploring the audience’s reception of the issue of sexual harassment of female workers presented in the movie. This incident sparked the researcher’s interest in exploring the audience’s reception of the issue of sexual harassment of female workers presented in the movie. Therefore, this study involved several female informants who work in various fields with diverse educational backgrounds and occupations. By using Stuart Hall’s reception theory analysis, this research aims to understand and position the audience towards the messages contained in the movie "Bombshell" (2019). The research method applied is descriptive qualitative with a constructivist paradigm. Data collection was done through in-depth interviews to get in-depth perceptions from each informant. The results showed that the four informants were in The Dominant Hegemonic-Code Position. Although there are differences in answers to some questions per scene, this variability is influenced by the diverse work and life backgrounds of each informant, including education and employment. Thus, this difference provides a broader context in evaluating the audience’s reception of the issue of sexual harassment raised in the movie "Bombshell" (2019).